Understanding and Managing the Emotional Labor of Qualitative Research - Carol Rogers-Shaw; Jinhee Choi; Davin Carr-Chellman (Forum: Qualitative Social Research, 2021)
To offer solutions for qualitative researchers who are working to overcome emotional labor, we have drawn on data from fieldwork focused on marginalized populations including mothers of children with disabilities, North Korean defectors, and educators working in under-resourced, remote rural school districts. It is important to recognize the significance of emotional labor in qualitative studies as its effects can have personal consequences for the researchers, can influence the experiences of vulnerable participant populations, and can shape data analysis. Through a tripartite form of autoethnography, we explored our own experiences of emotional labor. Based on field notes and discussions both during and after fieldwork, we investigated ways to overcome the burdens of emotional labor through personal, relational, and instructional approaches. By elaborating potential areas where scholars can protect themselves from difficulties and grow personally and collaboratively, our findings can help researchers, educators, and students better prepare themselves for investigating the challenges facing marginalized populations while promoting social justice and advocacy.